O estágio supervisionado como componente curricular na formação inicial e continuada do professor de Biologia - Brasil, Osimar Bezerra Magalhães (2012)
Dissertation Research that deals with the continuing education of Biology teachers, in an autobiographical approach. Assuming that the Supervised Curricular Internship is one of the curricular components in the Biology Degree Course, we ask: what is possible to be analyzed, based on the experiences obtained both during the Supervised Internship in initial training and in the training continued, in a formative trajectory of a professor of Biology? The methodology was constructed from the History of Life Method, which is constituted in the first part of Chapter -1, "On the choice of the Method of Life History", where we address, among other topics, "The researcher's self-knowledge in understanding the role social of the teacher ". In the second part, we address "The fundamentals of the formative trajectory of the researcher", highlighting the acquisition of a new posture: "the researcher professor". In chapter - 2, we address, in the third and fourth part, relevant aspects such as: "teacher training and education professionals" and "the researcher in the supervised curricular stage". Chapter - 3, in the fifth part, deals with the retrieval of the researcher's narratives during his undergraduate period, where aspects of the researcher's self - construction and teaching identity are highlighted. And, finally, in the sixth part: "Supervised Curriculum Internship in Continuing Education", we approach the legal presuppositions of the internship, the planning, the narratives of the practices performed and we weave our final considerations. Keywords: Teacher Training, Supervised Internship, Autobiography.